Curriculum Development Based on Environment for Sustainable Education - Marzuki, Kartini; Ansar, Ansar (Westscience Press, 2024)
This research aims to develop an environmental-based curriculum for sustainable education through literature review method. By integrating findings from various literature sources, this research aims to provide a solid foundation for the development of a relevant and effective curriculum in addressing environmental issues. The results of the literature analysis indicate that interdisciplinary approaches, critical thinking, concrete actions, ethical values, and collaboration are key to creating a curriculum oriented towards action and community engagement. Recommendations include involving more stakeholders in curriculum development, as well as conducting further research to evaluate the effectiveness of implementing this curriculum in various educational and environmental contexts. Gratitude is expressed to all parties who have provided support and contributions to this research.